1992
DOI: 10.3109/00365599209180879
|View full text |Cite
|
Sign up to set email alerts
|

Cost Effectiveness of Extracorporeal Shock Wave Lithotripsy and Percutaneous Nephrolithotomy for Medium-Sized Kidney Stones

Abstract: To evaluate percutaneous nephrolithotomy (PNL) and extracorporeal shock wave lithotripsy (ESWL) for their clinical effects, their cost effectiveness, their complication rates, and the patients' experiences, 55 consecutive patients were randomised to have one or other operation between October 1986 and October 1988. Six patients were excluded, 21 were treated with PNL and 28 with ESWL as primary treatment. Mean hospital stay and length of treatment were longer for PNL than for ESWL. Since 1 July 1987 all patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
5

Year Published

1995
1995
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 5 publications
2
10
0
5
Order By: Relevance
“…4) corresponded to a reduction from Aus$ 4748 to Aus$ 2374 per patient, albeit that such values do not consider changes in resource use per inpatient-day. These outcomes are generally consistent with results of other population-based research [16,17] and clinical trials of the cost-effectiveness of the noninvasive and minimally invasive treatment methods [10][11][12][13][14]. The third benefit has been the increased chance of renal preservation.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…4) corresponded to a reduction from Aus$ 4748 to Aus$ 2374 per patient, albeit that such values do not consider changes in resource use per inpatient-day. These outcomes are generally consistent with results of other population-based research [16,17] and clinical trials of the cost-effectiveness of the noninvasive and minimally invasive treatment methods [10][11][12][13][14]. The third benefit has been the increased chance of renal preservation.…”
Section: Discussionsupporting
confidence: 84%
“…That ESWL is used to treat most calculi in the upper urinary tract is not surprising, given that it has consistently out-performed even minimally invasive endourological procedures in clinical trials of costeffectiveness [10][11][12][13][14]. Moreover, patients prefer to avoid surgery in the treatment of stone disease, with ESWL being perceived by them as the most desirable treatment option [15].…”
Section: Introductionmentioning
confidence: 99%
“…In the study of Carlsson et al [16] the cost-effectiveness of SWL versus PNL in the treatment of LP stones was evaluated. They showed that SWL was less costly.…”
Section: Discussionmentioning
confidence: 99%
“…It is not yet possible to look at a film and select the proper treatment for upper-tract calculi, i.e., ESWL or percutaneous nephrolithotomy. This would be the more desirable, since it has been shown that the latter treatment is less expensive under certain circumstances [12].…”
Section: Discussionmentioning
confidence: 99%